Examining The Mediating Role of Electric Motorbike Purchase ‎Decisions in Medan City, Indonesia - Tirtayasa, Satria; Suhendi; Rahmadana, Muhammad Fitri; Simatupang, Maulida Putri (International Journal of Accounting and Economics Studies, 2025)
This study seeks to examine and evaluate the effects of brand awareness, pricing, and product quality on consumer purchasing decisions, ‎with perceived value acting as a mediating variable among electric motorbike users in Medan City. The target population comprises all ‎electric motorbike owners currently operating their vehicles in Medan, although the exact population size remains unspecified. A total of ‎‎100 respondents were selected as the research sample using the Lemeshow sampling method. Data were gathered through questionnaires, ‎where the researchers engaged directly with participants, and responses were collected via a Google Form. Analytical methods employed ‎in this study include descriptive statistics and path analysis using the Partial Least Squares (PLS) approach. The findings indicate that ‎brand awareness, price, and product quality each significantly affect purchasing decisions. While brand awareness does not significantly ‎impact perceived value, both price and product quality do. Furthermore, perceived value has a direct effect on purchasing decisions. However, when mediated by perceived value, brand awareness does not influence purchasing decisions, whereas both price and product quality-‎ty do‎.
Keywords: Brand Awareness; Price; Product Quality; Perceived Value; Purchase Decision